Mechanics of materials with embedded unstable molecules. (1st May 2019) - Brighenti, Roberto; Artoni, Federico; Cosma, Mattia Pancrazio
Highlights: Probabilistic-based micromechanical modeling of polymers is considered. Polymers with bi-stable molecules embedded in the chains network are studied. Molecule conformation change switching is triggered by chemical or mechanical stimuli. Mechanics of swelling is accounted for in the model. A continuum model is obtained from the micromechanical approach. Abstract: Active structural systems and materials, typically used to develop sensors or actuators, are those capable of responding to external stimuli with some physical detectable reactions. The triggering stimuli can be of various nature, ranging from temperature, pH, light, mechanical stress, etc. In this context, responsive materials have the capability to react at the molecular level, showing some changes in their microstructure that can be detected and measured at the meso- or macro-scale level. This ability can be obtained in polymers and polymer-like materials through the introduction in their network of switchable molecules, characterized by two geometrically distinct stable states, where the switch from one to the other can be seen as an instability phenomenon. In this research, we present a continuum mechanical model, developed starting from the micromechanics of the polymer network joined to molecules whose switching instability is induced by mechanical or chemical actions. The theoretical framework is presented by considering the general case of poly-disperse polymers and some final examples are given and discussed. The proposed model can be used as a tool for the development and design of smart responsive systems, applicable across a wide range of length scales.